JAGA DESA BERSIH YANG BERISI MATERI PEMBEKALAN UNTUK SISWA-SISWI DI SD 6 PADANG SAMBIAN KELOD DENGAN MENGURANGI, MEMANFAATKAN, DAN MENGGUNAKAN KEMBALI BARANG BEKAS MENJADI BARANG YANG BERNILAI - Darsana, I Gede Rawi; Widhya Sedana Putra, Komang (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This program was implemented at SD 6 PADANG SAMBIAN KELOD to provide real contributions to social and environmental development. This activity focuses on the “Keep the Village Clean” program in Padang Sambian Kelod, which aims to increase public awareness, especially children, in maintaining environmental cleanliness. This program was implemented through briefing activities at SD 6 Padang Sambian Kelod with the main material on the concept of reduce, reuse, recycle (reducing, reusing, and recycling) used goods so that they have a higher utility value. Children were given education on the importance of maintaining village cleanliness and were taught creative ways to process used goods into useful products. Through an educational and interactive approach, this activity succeeded in increasing students’ understanding of better waste management. The evaluation results showed that active student participation in this activity can encourage positive behavioral changes in maintaining the cleanliness of the school and village environment. With this program, it is hoped that public awareness of the importance of environmental cleanliness will increase and can be sustainable in the future.